Efforts to Improve Football Passing Skills Through The Cat-Cat Playing Method - Harfian Dwi Kusuma Atmaja; Gatot Jariono; Nur Subekti (Universitas PGRI Palembang, 2025)
In Physical Education learning, there are several obstacles that occur in the learning process of passing football in grade V students of SDN Sondakan, Laweyan District, Surakarta City. One way that can be done to improve learning is to create a learning model that is interesting for students, namely through a play approach. The problem in this study is whether the implementation of passing learning using cat games can improve the passing skills of grade V students of SDN Sondakan. The purpose of this study is to find out if the application of learning through the media of cat games can improve football passing skills using the inner legs of grade V students of SDN Sondakan in physical education subjects. This research was conducted at SDN Sondakan with a sample of 26 students in class V. This research is a classroom action research consisting of two cycles where each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. The data collection techniques in this study are: observation method and test method. The results of the study show that the application of the cat-cat playing method can improve football passing skills in grade V students of SDN Sondakan. From the results of the analysis obtained, there was an increase from pre-cycle to cycle 1 and then to cycle 2. The conclusion of this study is that passing learning through the cat-cat playing method in grade V students of SDN Sondakan can improve students' football passing skills.